Zones of Tayler Instability in Stars - Valentin A. Skoutnev; Andrei M. Beloborodov (The Astrophysical Journal)
The Tayler instability (TI) of toroidal magnetic fields is a candidate mechanism for driving turbulence, angular momentum (AM) transport, and dynamo action in stellar radiative zones. Recently V. A. Skoutnev & A. M. Beloborodov (2024) revisited the linear stability analysis of a toroidal magnetic field in a rotating and stably stratified fluid. In this paper, we extend the analysis to include both thermal and compositional stratification, allowing for general application to stars. We formulate an analytical instability criterion for use as a “toggle switch” in stellar evolution codes. It determines when and where in a star the TI develops with a canonical growth rate as assumed in existing prescriptions for AM transport based on Tayler–Spruit dynamo. We implement such a toggle switch in the MESA stellar evolution code and map out the stability of each mode of the TI on a grid of stellar evolution models. In evolved lower-mass stars, the TI becomes suppressed in the compositionally stratified layer around the hydrogen-burning shell. In higher-mass stars, the TI can be active throughout their radiative zones but at different wavenumbers than previously expected.